2016
DOI: 10.18632/oncotarget.8580
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase iota (Pol ι) promotes invasion and metastasis of esophageal squamous cell carcinoma

Abstract: DNA polymerase iota (Pol ι) is an error-prone DNA polymerase involved in translesion DNA synthesis (TLS) that contributes to the accumulation of DNA mutations. We recently showed that Pol ι is overexpressed in human esophageal squamous cell cancer (ESCC) tissues which promotes ESCC' progression. The present study was aimed at investigating the molecular mechanisms by which Pol ι enhances the invasiveness and metastasis of ESCC cells. We found that the expression of Pol ι is significantly higher in ESCCs with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…(14,15) We also found that Pol ι promotes invasiveness and migration of ESCC cells in vitro. (15) However, the process of Pol ι-mediated invasion and metastasis of ESCC cells is not well understood. To explore the potential mechanisms responsible for Pol ι-mediated metastasis, RNA-Seq transcriptome analysis was performed using RNA isolated from Pol ι-knocking down and control ESCC cells.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…(14,15) We also found that Pol ι promotes invasiveness and migration of ESCC cells in vitro. (15) However, the process of Pol ι-mediated invasion and metastasis of ESCC cells is not well understood. To explore the potential mechanisms responsible for Pol ι-mediated metastasis, RNA-Seq transcriptome analysis was performed using RNA isolated from Pol ι-knocking down and control ESCC cells.…”
mentioning
confidence: 55%
“…Our previous work demonstrated that the expression level of Pol ι is closely associated with tumor progression and poor prognosis of ESCC . To confirm the correlated expression among Pol ι, ETS‐1 and ETS‐1 phosphorylation at threonine‐38, immunohistochemical staining was performed in 93 ESCC tissues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations